Evaluation of the Physical Condition and Death Mechanisms of Cancer Patients in Their Terminal Stage - Chkhaidze, Mikheil; Tkeshelashvili, vas (Caucasus Journal of Health Sciences and Public Health, 2020)
Based on ASCO (2019), death from cancer occurs after a patient becomes weaker and more exhausted in a matter of weeks or months. Of course, it is hard to predict the term of living; but, some general signs and symptoms show that the person is entering the phase, where only final weeks and days are left. The fact that we already know about our expectations, we can work on releasing anxieties and properly planning the remaining time.